Prototype development of solid ankle cushion heel (sach) prosthetic foot - Wan Syahira, Wan Ramli; Azizan, Ramli; Mohd Shaiful Zaidi, Mat Desa; Azuan Failani, Ariffin; Mohd Sharol Helmi, Mat Desa (2021)
The product is very high quality with the combination of new materials, polyurethane and neoprene that give unique characteristics at low cost and safe. The product have been design that assist by proffesional person and applicable to be used by user/patients.